10-Gb/s limiting amplifier and laser - Galal, S.
A limiting amplifier incorporates active feedback, inductive peaking, and negative Miller capacitance to achieve a voltage gain of 50 dB, a bandwidth of 9.4 GHz, and a sensitivity of 4.6 mVpp for a bit-error rate of 10-12 while consuming 150 mW. A driver employs T-coil peaking and negative impedance conversion to achieve operation at 10 Gb/s while delivering a current of 100 mA to 25-Ω lasers or a voltage swing of 2 Vpp to 50-Ω modulators with a power dissipation of 675 mW. Fabricated in 0.18-μm CMOS technology, both prototypes operate with a 1.8-V supply.
Keywords: 0.18 micron; 1.8 V; 10 Gbit/s.; 100 mA; 150 mW; 25-fi lasers; 50 dB; 50-fi modulators; 675 mW; 9.4 GHz; CMOS technology; T-coil peaking; Active feedback; Bit-error rate; Broadband amplifiers; Inductive peaking; Laser drivers; Laser/modulator driver; Limiting amplifier; Limiting amplifiers; Negative Miller capacitance; Negative impedance conversion; Power dissipation; Sensitivity; Voltage gain; Voltage swing